Efectul unor plante medicinale asupra profilului lipidic și al activității enzimelor hepatice în comparație cu statinele - Mohamed, Erieg Abdul Wahab; Cristina, Romeo T. (Medicamentul Veterinar, 2017)
In the recent decades, hyperlipidemia has considerably increased with the development of machine life. It has been accompanied by diseases such as hypothyroidism, liver and kidney diseases, diabetes, chronic kidney disease, as well as obesity and can cause complications such as atherosclerosis, hypertension, increased risk of stroke, and fatty liver disease. Currently, the prevalence of hyperlipidemia and its related diseases has increased in developing as well as developed countries. In the most cases, drug therapy is needed to control and treat hyperlipidemia. However, problems related to conventional drugs including adverse events (digestive complications such as indigestion, bloating, constipation along with neurologic complications such as myopathy and neuralgia. In addition to the hepatotoxicity and nephrotoxicity). Growing rate of hyperlipidemia and its related complications despite the availability of these drugs dissatisfaction of patients with these drugs, emergence of complications induced by their prolonged use, as well as high drug costs have increased tendency to complementary and alternative treatments for the control and treatment of this disease. In this regard, traditional medical information of each region as well as identification and utilization of medicinal plants of that area may have an important role in identifying new medicines with plant origin for alternative treatments. In addition to endogenous antioxidants, there are exogenous antioxidants. The beneficial effects of foods have been linked to the presence of bioactive compounds and other nutrients. Examples of biomolecules that have antioxidant potential are phenolic compounds such as isoflavones, phenolic acids, catechins, chlorogenic acids, anthocyanins, and terpenes. Thus, plants have been described as an alternative to the development of new drugs applied to treatment of many diseases such as hypercholesterolemia, ulcers, depurative blood and cancer.